Sweden's New Resettlement Policy: Introducing Gender and Gender Equality as Governing Tools in Migration Governance - Suter, Brigitte (Refuge, 2026)
In 2022, Sweden introduced new refugee selection guidelines prioritizing women and girls—a departure from earlier practices focused solely on vulnerability. Through a problem representation analysis, this article examines parliamentary motions on resettlement from 2015 to 2022, exploring how gender, im/mobility, religion, and vulnerability shape notions of deservingness. It argues that gender is—intentionally or not—used as a governance tool, reflecting a broader migration policy shift of not only framing men and asylum seekers as a problem but creating the grounds for weakening rights-based approaches in favour of a more humanitarian approach to migration governance driven by compassion but also control.